N-Acetyl Cysteine Restores Limb Function, Improves Mitochondrial Respiration, and Reduces Oxidative Stress in a Murine Model of Critical Limb Ischaemia - Lejay, Anne; Paradis, Stéphanie; Lambert, Aude; Charles, Anne-Laure; Talha, Samy; Enache, Irina; Thaveau, Fabien; Chakfe, Nabil; Geny, Bernard (European Journal of Vascular and Endovascular Surgery, 2018)
The aim of this study was to investigate whether antioxidant therapy might decrease oxidative stress related deleterious effects in the setting of critical limb ischaemia (CLI). Twenty Swiss mice were submitted to sequential right femoral and iliac ligatures; the left limb served as control. The mice were assigned to two groups: in the first group (no-treatment group, n = 10) no treatment was administered; in the second group (N-acetyl cysteine [NAC] group, n = 10) NAC was administered by dissolution in drinking water for 4 weeks, starting on day 7, when CLI was effective. Clinical and functional scores were assessed by two blinded investigators. Mice were killed on day 40 and mitochondrial respiratory chain complex activities, calcium retention capacity, oxidative stress, and histological analysis were analysed. Ischaemic muscles in the no-treatment group showed significantly impaired mitochondrial respiration and calcium retention capacity, with increased production of reactive oxygen species; but no statistical difference was noticed when comparing ischaemic muscles in the NAC group (n = 10) to contralateral muscles (n = 10) and to control muscles in the no-treatment group (n = 10). Ischaemic muscles in the no-treatment group exhibited myopathic features such as wider range in fibre size, rounded shape, centrally located nuclei, and smaller cross sectional areas, but none of these features were observed in contralateral muscles or in NAC-group muscles (ischaemic or controls). Targeting inhibition of oxidative stress may be a potential therapeutic strategy for muscle protection in CLI and might be considered as potential adjunctive therapy to revascularisation procedures.